Using LoRa Technology for IoT Monitoring Systems - Christos Bouras; Apostolos Gkamas; Vasileios Kokkinos; Nikolaos Papachristos (10th International Conference on the Network of the Future (NoF 2019), Rome, Italy, 2019)
This paper presents technology comparison scenarios for Internet of Things (IoT) concepts on rescue monitoring. The study starts by comparing WiFi & LoRa as wireless technologies able to be used by smart devices for data transmission. The IoT end-devices used in these concepts have high requirements in battery saving and for this reason the usage of low-power modules is advisable. This paper focus in rescue monitoring and the goal in the current study is the usage of the two wireless technologies used for data transmission from IoT devices: the already known WiFi and the upcoming LoRa technology. During rescue monitoring, important concepts are the identification and individuals' rescue of particularly vulnerable groups or individuals belonging to population groups with a high probability of being lost. A LoRa based gateway and WiFi Router is used to connect the end-devices used in our scenarios to the Internet. The collected data on server application as captured from installed sensors on the IoT modules can be displayed to authorized users through a web or mobile application. The results through simulation and real time experiments indicate that LoRa could be an ideal candidate for rescue monitoring. This study is a first step in creating a more general ecosystem for rescue concepts including all the hardware and software using the LoRa technology as transmission method.